OPTIMALISASI PELAKSANAAN PEMBELAJARAN BINA WICARA UNTUK MENDUKUNG KEMAMPUAN KOMUNIKASI ANAK TUNARUNGU - Hermanto, Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Communication ability of deaf children has not reached maximum result yet generally as their parent’s hope although getting the instructional of bina wicara in school. The maximum unreachable ability of these deaf-children’s communication is influenced by some factors namely The main factor,surely,is on the children condition themshelves namely the limitation of vocabulary, low control ability of sound perception and rythm, immature of articulation ability, and low mastering in total communication. Second, the teacher’s low ability and skill in bina wicara instructional. Third, lack of supporting facilities of bina wicara instructional. Fourth, lack of cooperation among teachers in supporting communication ability of deaf children. From some factors that obstacle the communication ability of deaf-children,so, it must be togather-awareness and to be solved soon. Because of that, the optimalization of bina wacara instructional implementation becomes a key to support the result and communication ability of deaf children.